1992
DOI: 10.1002/j.1537-2197.1992.tb13655.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Injury During Floral Development in Cowpea (Vigna Unguiculata, Fabaceae)

Abstract: High night temperatures during floral development induce male sterility in cowpea (Vigna unguiculata [L.] Walp.). The objectives of this study were to determine: the possible causes of the male sterility; the stage of floral development when damage due to heat stress occurs; and whether specific tissues are damaged during the period of sensitivity to heat. Plants were grown under controlled temperatures in both greenhouses and growth chambers in separate experiments. Floral development was normal under a night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
111
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 24 publications
(33 reference statements)
7
111
0
3
Order By: Relevance
“…In chickpea, development of male (pollen/anther) and female (stigma, style, and ovary) reproductive organs is most sensitive to abiotic stress [52]. High temperature has a particularly detrimental effect on two stages of pollen development: meiosis in the microspore mother cell and mature microspores [53][54][55]. Heat stress could also affect the development of tapetal cells, resulting in degeneration and premature development of pollen in the case of cowpea and snapbean [54,55].…”
Section: Effect Of Heat Stress On Chickpeamentioning
confidence: 99%
See 1 more Smart Citation
“…In chickpea, development of male (pollen/anther) and female (stigma, style, and ovary) reproductive organs is most sensitive to abiotic stress [52]. High temperature has a particularly detrimental effect on two stages of pollen development: meiosis in the microspore mother cell and mature microspores [53][54][55]. Heat stress could also affect the development of tapetal cells, resulting in degeneration and premature development of pollen in the case of cowpea and snapbean [54,55].…”
Section: Effect Of Heat Stress On Chickpeamentioning
confidence: 99%
“…High temperature has a particularly detrimental effect on two stages of pollen development: meiosis in the microspore mother cell and mature microspores [53][54][55]. Heat stress could also affect the development of tapetal cells, resulting in degeneration and premature development of pollen in the case of cowpea and snapbean [54,55]. Pollen germination in chickpea is optimal at 25 C and germination is reduced under heat stress conditions, leading to reduced fertilization [56,57].…”
Section: Effect Of Heat Stress On Chickpeamentioning
confidence: 99%
“…Artificial pollination studies demonstrated that pistil viability was not affected by high night temperatures (Warrag and Hall 1983). Reciprocal transfers of plants between growth chambers with high or optimal night temperatures demonstrated that the stage of floral development most sensitive to heat stress occurred 9-7 days before anthesis (Ahmed et al 1992). This is after meiosis, which occurs 11 days before anthesis and about the same time that the tetrads are released from the microspore mother cell sac (Warrag and Hall 1984b;Ahmed et al 1992;Mutters and Hall 1992).…”
Section: Heat Stress Effects In Subtropical Zonesmentioning
confidence: 99%
“…Reciprocal transfers of plants between growth chambers with high or optimal night temperatures demonstrated that the stage of floral development most sensitive to heat stress occurred 9-7 days before anthesis (Ahmed et al 1992). This is after meiosis, which occurs 11 days before anthesis and about the same time that the tetrads are released from the microspore mother cell sac (Warrag and Hall 1984b;Ahmed et al 1992;Mutters and Hall 1992). Premature degeneration of tapetal tissue and lack of endothecium formation were observed, which could have been responsible for the low pollen viability, low anther dehiscence, and low pod-set under high night temperatures (Ahmed et al 1992).…”
Section: Heat Stress Effects In Subtropical Zonesmentioning
confidence: 99%
See 1 more Smart Citation